A protocol for rapid and high-frequency in vitro propagation of solanum nigrum L. - Zou, Li-Juan; Yang, Jing-Tian; Wu, Qing-Gui (Penerbit Universiti Kebangsaan Malaysia, 2017)
Solanum nigrum L. is a species highly valued for its medicinal properties. In the present study, an efficient propagation system was established by using five explants of S. nigrum namely, roots, leaves, rooted hypocotyls, nodal segments and petioles. Various types of plant growth regulators (PGRs) were used to determine the most effective hormone combination for callus induction and organogenesis. Zeatin (ZT), thidiazuron (TDZ), kinetin (Kin) and indole-3-acetic acid (IAA) were found to induce multiple shoots. Shoot organogenesis was induced in the five explants. The highest mean for number of shoots per petioles (31.54±5.76) and rooted hypocotyls (44.00±1.51) with a 100% induction rate was obtained on Murashige and Skoog (MS) medium fortified with 0.4 mg/L IAA and 3.0 mg/L ZT. MS medium containing 0.4 mg/L IAA and 3.0 mg/L TDZ was found to be optimal for shoot regeneration of roots, leaves and nodal segments. The highest regeneration frequency (100%) with mean numbers of shoots equal to 38.77±6.87 for roots, 42.73±7.75 for leaves and 56.73±7.98 for nodal segments was produced. Regenerated shoots rooted effectively on half-strength MS medium and acclimatized successfully in soil with a 100% survival rate and normal growth. The protocol can be used for the large-scale propagation of S. nigrum to meet the increasing demand of commercial cultivation.